Kontrol Traksi Elektronik Untuk mengatasi slip Pada kendaraan Bermotor - Perpustakaan UGM, i-lib ([Yogyakarta] : Kantor Wakil Rektor Bidang Kemahasiswaan dan Alumni UGM, 2003)
Differential is designed to enable car to turn easily because differential permits one wheel to turn faster than the other. However, the differential has disadvantage when one of the wheels is caught into muddy, slippery or icy road, makes this wheel have no traction to move the car. In order to make the car moves forward, the loosing traction wheel should be braked so that the engine torque can be transmitted to the other wheel. In this research, the electronic traction control simulator was build. This simulator employed ATMEL 90S8535 microcontroller for controlling task. The wheel rotation was sensed by inductive proximity sensors. This simulator works according this sequence, if one of the wheels get slip, automatically this wheel will be braked so that the other wheel can start to rotate. This rotation causes the car can move forward.